KEPEMIMPINAN VISIONER PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) BERDASARKAN KEPMENDAGRI NOMOR 47 TAHUN 1999 - Hanfan, Ahmad; Sumarno, , (PERMANA, 2010)
Perusahaan Daerah Air Minum (PDAM)  Is a public  company whlch  service to fulfill  amount of water required.   It is in accordance    with  the mandate  of article   37 of Government   Regulation number 16 Year  2005 about  the development of water supplying  system.   PDAM  actually is not single  operator.  because the  cooperation   and  private  enterprise  could  also  be the operator or organizer.   Because  or  Initial  Investment   is very big,   It  Is  rarely that  cooperation    and  private enterprise join with   the water  supplying    system business.    Due to it is semi-monopoly; the goverment should make the rule/regulatlon     which aim to protect consumers  /the  public  as customer. Rule/Regulatlons   of the government   must restrict  the authority of the taps  as profit oriented enterprise. To overcome   these oustacles,    PDAM requires   the  director or  manager who gass the  soul of a visionary leadership.    Hopefully, with  the visionary   manager/leader   who can face the obstacles that  exist  so that he can  lead  the company  more  advanced  againKeyword:  Visionary   Leadership